Dementia in Parkinson's disease: a Brazilian sample - Beatriz Baldivia; Sonia Maria Dozzi Brucki; Silmara Batistela; Juliana Carvalho Esper; Cristiano Duarte Augusto; Maria Sheila Guimarães Rocha (Arquivos de Neuro-Psiquiatria)
To determine the prevalence of dementia associated with Parkinson's disease (PD-D) in a Brazilian sample adopting clinical and diagnostic procedures recommended by the Movement Disorders Society (MDS). Sixty-seven patients were consecutively submitted to neurological, neuropsychological and functional examinations. PD-D was established according to MDS clinical criteria (Level II) and clinical procedures for PD-D (Level I) and prevalence rate was compared between the levels adopted. Ten patients (14.9%) were diagnosed as demented by Level I criteria whereas sixteen (23.8%) were diagnosed based on Level II criteria. Level I criteria had low sensitivity in detecting PD-D (31.25%), but greater specificity (90.19). The PD-D group had significantly worse performance on all neuropsychological tests, were older (p<0.001), had an older age of onset ofdisease (p<0.01), had lower educational level (p<0.02) and had higher scores on functional scales. Current age (p=0.046) and Hoehn & Yahr score (p=0.048) were predictors for developing PD-D.